STRATEGI GURU DALAM MANAJEMEN KELAS PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI SDN PEJUANG 7 - Pradevi, Yuliana Elsa; Muhammad Rijal Fadli; Nurul Febrianti; Khusnul Fatonah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the problem of ineffective classroom management in Pancasila Education learning in class III D of SDN Pejuang 7, characterized by a monotonous and teacher-centered approach resulting in a less conducive classroom atmosphere and less active student involvement. The purpose of the study is to analyze teacher strategies in classroom management through three sub-focuses: student arrangement, discipline management, and the creation of a learning atmosphere on the topic